Az egészségügyi szimulációs oktatás jelene és jövője Magyarországon - Bogár Péter Zoltán; Tóth Luca; Rendeki Szilárd; Mátyus László; Németh Norbert; Boros Mihály; Nagy Bálint; Nyitrai Miklós; Maróti Péter (2020)
Simulation-based medical education aims to model clinical situations and tasks using simulators, computers or even human beings. By using this system, the students are able to learn and master technical, also non-technical skills in lifelike situations. This publication contains a historical review of simulation-based education system, and its actualities in Hungary. Simulation has an unquestionable role in medical education. It is beneficial for the students, for the teachers, and for the teaching hospitals as well, since it saves clinical equipment and reduces the human burden. Its main purpose is to establish connection between theoretical and practical competencies, preparing the students for real medical challenges. Simulation has been a known teaching method for centuries, but only the 21st century brought real breakthrough due to the sudden development of technology. As a result of the recent years' innovative development and accepted innovative solutions, the modeling of complex medical procedures turned into more realistic. In Hungary, 3D-printed tools, virtual reality and augmented reality approaches are already adopted for education purposes. The national simulation network contains 3 universities and 16 hospitals. The initial developments are shown to be successful, as simulation-based training is progressively involved in undergraduate and post-graduate education, and the overall feedback is positive from the involved students. The evolvement of comprehensive national methodology for education has started also, by publishing reference books. This review is about the state of the national simulation education and offers development possibilities. Orv Hetil. 2020; 161(26): 1078-1087.